2008
DOI: 10.1007/978-3-540-76280-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and Interactive Approaches to Document Analysis

Abstract: Summary. This chapter explores three aspects of learning in document analysis: (1) field classification, (2) interactive recognition, and (3) portable and networked applications. Context in document classification conventionally refers to language context, i.e., deterministic or statistical constraints on the sequence of letters in syllables or words, and on the sequence of words in phrases or sentences. We show how to exploit other types of statistical dependence, specifically the dependence between the shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…This raises several interesting possibilities, for instance, the incorporation of human expert knowledge in a potential solution by means of human machine interaction. Interactive learning could be another possible direction [92].…”
Section: Connectionsmentioning
confidence: 99%
“…This raises several interesting possibilities, for instance, the incorporation of human expert knowledge in a potential solution by means of human machine interaction. Interactive learning could be another possible direction [92].…”
Section: Connectionsmentioning
confidence: 99%
“…Again using four folds at a time for training, we estimated the parameter α from Eq. (18). We then solved the IP for the test fold and applied the error correction procedure of Section 4, often resulting in dramatic increases in word accuracy.…”
Section: Cross Validationmentioning
confidence: 99%
“…For example, in a long document, the most common symbol is usually the letter "e", but in a road sign, any letter could be most common. This makes it difficult to use cryptographic techniques [13,3,2,4,18]. Finally, many signs are meant to be eye-catching, and are for this reason designed with stylized, whimsical, or otherwise unusual fonts for which we are unlikely to have matching training data.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning approaches require a very large document sample that we were unable to get, so the knowledge engineering approach was expedient 32008). This human interaction has been categorized as human‐initiated or machine‐initiated , and described as durable (when used to alter system parameters) or ephemeral (when used to label patterns or modify results, for instance) (Nagy & Veeramachaneni, 2008, p. 237).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that human interaction in the process is more effective when interspersed with the algorithmic process rather than when relegated to only before or after the automated parts (Nagy & Veeramachaneni, 2008). This human interaction has been categorized as human‐initiated or machine‐initiated , and described as durable (when used to alter system parameters) or ephemeral (when used to label patterns or modify results, for instance) (Nagy & Veeramachaneni, 2008, p. 237).…”
Section: Introductionmentioning
confidence: 99%